Green Product and Process Innovation, Corporate Environmental Ethics and Competitive Advantages among Manufacturing Firms in the Kingdom of Saudi Arabia - Tai Abdulrahman Alshammari; Khalid Mhasan Alshammary; Fahad Maiyah Alshammari (Journal of Economics and Behavioral Studies, 2022)
The prime objective of the study is to examine the impact of green product innovation, green process innovation, and corporate environmental ethics on the competitive advantages of Saudi manufacturing firms. In addition to that, the study has also planned to examine the mediating role of corporate environmental ethics and moderating role of corporate environmental management in the relationship between green product innovation, green process innovation, and competitive advantages of Saudi manufacturing. This study used a quantitative approach to research with a cross-sectional method for the collection of data. This study used purposive sampling for the collection of data from the production managers of the manufacturing industry of KSA. The participation of the production managers in current was on a volunteer base. A structured questionnaire was used to gather the data from the respondents. The scale item for all constructs was adapted from the previous studies and measured on a 5-point Likert scale. “Partial Least Squares” (PLS) method of analysis was employed for the analysis of the research model using the Smart-PLS (Ringle et al., 2020). The present study found out that if a firm is consistent about investing more in CEE, the KSA manufacturing industry would witness improvement in their GRpdI and competitive advantage. Thus, these findings can be utilized by the manufacturing industries in KSA. By observing the environmentalism approach of consumers and strict rules at the international level, the firms shouldn’t avoid their environmental duties. This study intends to fulfill the purpose of contributing to managers of the manufacturing industry of KSA, their researchers and policy formulators which may further contribute to their respective areas.